Effective guest complaint management for hotel front office staff: Active listening, prompt resolution, empathy, and consistent follow-up - Sudiarta, Made; Santra, I Ketut; Hakim, Jumhur (Journal of Commerce, Management, and Tourism Studies, 2025)
Effective complaint management in the hospitality industry, particularly within the front office operations of hotels, plays a critical role in ensuring guest satisfaction, fostering loyalty, and maintaining a positive brand reputation. As the primary point of contact, front office staff are frequently tasked with resolving guest grievances that vary in complexity and urgency. This article explores the best practices for managing guest complaints by front office personnel in hotels, drawing from both empirical research and industry standards. The study aims to identify key strategies, communication techniques, and behavioral competencies that contribute to successful complaint resolution. Utilizing a mixed-methods approach, the research combines qualitative interviews with hotel front office managers and quantitative analysis of guest satisfaction data across mid-range and upscale hotel properties. The findings reveal that proactive communication, emotional intelligence, timely response, empowerment of front-line staff, and follow-up procedures significantly enhance complaint handling effectiveness. Additionally, the integration of technology—such as CRM systems and real-time feedback tools—has been found to support efficiency and personalization in service recovery processes. The article further discusses the implications of complaint management practices on operational performance, employee training programs, and overall guest experience. Best practices identified through the research are synthesized into a practical framework to guide hotel managers and front office teams in handling complaints systematically and empathetically. The paper concludes by emphasizing the necessity of a complaint-positive organizational culture and continuous professional development to sustain service excellence in the competitive hospitality landscape.